PSORIATIC ARTHRITIS: CLASSIFICATION, CLINICAL PRESENTATION, DIAGNOSIS, TREATMENT - T. V. Korotaev; Yu. I. Korsakova (Научно-практическая ревматология, 2018)
soriatic arthritis (PsA) is a chronic inflammatory disease of the joints, spine and entheses from a group of spondyloarthritis (SpA), which is usually observed in patients with psoriasis (Ps). The diagnosis of PsA is based on the CASPAR criteria for psoriatic arthritis. The disease results from interactions between genetic, immunological and environmental factors. The main clinical manifestations of PsA include peripheral arthritis, enthesitis, dactylitis, and spondylitis. PsA must be differentiated from rheumatoid arthritis, gout, reactive arthritis, osteoarthritis, and ankylosing spondylitis. Due to the fact that PsA is a clinically heterogeneous disease, its activity is assessed using complex indices, by taking into account that the patient has arthritis, enthesitis, dactylitis, and spondylitis. The goal of treatment for PsA is to achieve remission or minimal activity of the main clinical manifestations of the disease, to slow down or prevent radiographic progression, to increase life expectancy and quality of life in the patients, and to reduce the risk of comorbidities, which is achieved through a wide range of drugs of different classes. Therapy should be chosen based on the clinical manifestations of PsA and comorbidities in the patients.